Hepatocellular carcinoma in a non-cirrhotic liver of a HCV-positive woman with sustained viral response - Gianfranco Costanzo; Genoveffa Balducci; Massimo Marignani; D'Arca Teresa; Lorenzo Nosotti; Concetta Mirisola (Mediterranean Journal of Hematology and Infectious Diseases)